The Role of Strategy Planning to Achieve Organizational Goals in Uncertainty Situations in MSMES in Indonesia - Hartono Subagio (Return : Study of Management, Economic and Bussines, 2024)
In Uncertainty Situations Various efforts and support have been made by the government to protect its people from various sectors. This article will discuss the strategic management of MSMEs in dealing with the impact of the pandemic on the Emergency PPKM policy. The purpose of this article is to find out the right MSME strategy during the current pandemic. This article uses a qualitative descriptive research method through a literature approach. The results of this research show that strategies that can be used by MSMEs in dealing with the pandemic and emergency PPKM policies include (1) digital marketing strategies. (2) strategy to improve services based on creative innovation (3) strategy to improve the quality of human resources.